Yeast proteins Gar1p, Nop1p, Npl3p, Nsr1p, and Rps2p are natively methylated and are substrates of the arginine methyltransferase Hmt1p. Issue 18 (10th August 2015) - Yagoub, Daniel; Hart‐Smith, Gene; Moecking, Jonas; Erce, Melissa A.; Wilkins, Marc R.
Abstract : The Hmt1 methyltransferase is the predominant arginine methyltransferase in Saccharomyces cerevisiae . There are 18 substrate proteins described for this methyltransferase, however native sites of methylation have only been identified on two of these proteins. Here we used peptide immunoaffinity enrichment, followed by LC‐ETD‐MS/MS, to discover 21 native sites of arginine methylation on five putative Hmt1 substrate proteins, namely Gar1p (H/ACA ribonucleoprotein complex subunit 1), Nop1p (rRNA 2'‐O‐methyltransferase fibrillarin), Npl3p (nucleolar protein 3), Nsr1p (nuclear localization sequence‐binding protein), and Rps2p (40S ribosomal protein S2). The sites, many of which were found to be mono‐ or di‐methylated, were predominantly found in RGG (Arg‐Gly‐Gly) motifs. Heavy methyl‐SILAC validated the majority of these peptides. The above proteins, and relevant sites of methylation, were subsequently validated by in vitro methylation with recombinant Hmt1. This brings the total of Hmt1 substrate proteins for which native methylation sites have been identified to five.